ANALISIS PENGARUH KARAKTERISTIK KOMITE AUDIT DAN PROFITABILITAS TERHADAP TIMELINESS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI) - Purbasari, Mirani; Rahardja, Rahardja (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of audit committee characteristics and profitability (ROA) of the occurence of timeliness. Characteristic of audit committee can be seen from size of audit committee, the composition of non-executive directors in audit committee, frequency of audit committee meeting and financial literacy of audit committee.The population in this study is all manufacture firms listed in Indonesia Stock Exchange periode 2010-2012. Sample of this research is 63 manufacture firms listed in Indonesia Stock Exchange periode 2010–2012 that selected by using purposive sampling method. Data analysis using logistic regression at levels significance 5%.The result showed that the number of financial literacy on the audit committee and profitability (ROA) significantly affect timeliness of financial reporting of the firm, while variable the size of audit committee, the composition of non-executive directors in audit committee, and frequency of audit committee meeting not have an affect to timeliness of financial reporting of the firm listed in Indonesia Stock Exchange.